2015
DOI: 10.1016/j.jor.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Brown-Sequard syndrome produced by calcified herniated cervical disc and posterior vertebral osteophyte: Case report

Abstract: Brown-Sequard syndrome (BSS) produced by hemisection of the spinal cord will lead to ipsilateral motor weakness, proprioceptive and vibratory sensation loss and is associated with contralateral deficit in sensation of pain and temperature. BSS is most commonly caused by injuries and neoplasms in the cervical and thoracic region.1-5 BSS induced by disc disorders is rare; since the first published case in 1928, only 50 cases have been reported in English language literatures. 6-10This case is the 51st published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The most common causes of BSS are traumatic injury and spinal cord tumor 1 , 10 , 12) . CDH is a relatively rare cause of BSS 3 , 6) and only few reports of BSS caused by CDH have been published until now 9) …”
Section: Discussionmentioning
confidence: 99%
“…The most common causes of BSS are traumatic injury and spinal cord tumor 1 , 10 , 12) . CDH is a relatively rare cause of BSS 3 , 6) and only few reports of BSS caused by CDH have been published until now 9) …”
Section: Discussionmentioning
confidence: 99%
“…Other rarer complications may result from external compression of the trachea [16, 17], the bronchi [18], the adjacent arteries [1922], and nerves [23, 24]. Furthermore, chronic throat symptoms [25], back pain [26], Brown-Sequard syndrome [27], Horner syndrome [28], intracranial hypotension [29, 30], chronic obstructive pneumonia [31], traumatic thoracic aortic rupture [32], esophageal perforation [33], and acute urinary retention [34] have been described as osteophytic complications. As far as heart complications are concerned, a traumatic heart perforation [35] and two cases of left atrial deformation by large osteophytes [26, 36] have been so far reported.…”
Section: Discussionmentioning
confidence: 99%
“…Early surgical intervention is positively correlated with better outcomes, most often resulting in significant improvement of symptoms to full recovery. 3,4,6,7,[9][10][11][12] In one case report, surgical intervention did not result in a significant improvement, and the patient had been suffering from progressive symptoms for 7 years prior to diagnosis and treatment. 11 Conservative Management.…”
Section: Treatmentmentioning
confidence: 99%